2022
DOI: 10.3390/agriculture12040471
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Analysis of Spike Segment of Special Tractor Wheels in Terms of Design Improvement for Chernozem Soil

Abstract: The driving wheels affect the tractive efficiency, fuel consumption, and soil compaction. This study presents the fatigue analysis of a spike segment that is the main part of an innovative driving wheels designed to improve tractor tractive performance. The design improvement was proposed for Chernozem soil allowing the full penetration of spikes. The spike segment was loaded by forces resulting from the maximum drawbar pull at 100% wheel slip and penetrometer resistance. A drawbar pull increase caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The device was developed and continuously improved at the Slovak University of Agriculture in Nitra (Slovak Republic) and allows for the setting of the active or inactive spike position. The design of this device is based on the fatigue analysis of a spike segment published in reference [26] and on a previous design version published in reference [27]. The fatigue analysis showed that the diameter of the horizontal rod connecting the left and right arms (Figure 2d,e) can be reduced from 12 mm to 10 mm.…”
Section: Spike Device With Worm Gear Unitmentioning
confidence: 99%
“…The device was developed and continuously improved at the Slovak University of Agriculture in Nitra (Slovak Republic) and allows for the setting of the active or inactive spike position. The design of this device is based on the fatigue analysis of a spike segment published in reference [26] and on a previous design version published in reference [27]. The fatigue analysis showed that the diameter of the horizontal rod connecting the left and right arms (Figure 2d,e) can be reduced from 12 mm to 10 mm.…”
Section: Spike Device With Worm Gear Unitmentioning
confidence: 99%
“…The samples of the soil were dried in an electric oven, and was kept at 105 • C for 24 h. The dried samples of the soil were re-weighed, and the weight was again noted in order to calculate the levels of the initial soil moisture content based on a dry weight and initial soil bulk density. Two agricultural tractors were used in the tillage experiments for measuring the horizontal force (draft) of the chisel plow, as is described in [6,[43][44][45][46][47][48]. In the first and second experimental sites, the chisel plow under study was mounted at the rear of Ford tractor (main tractor) model TW15 with a diesel engine of 110 kW at 2300 rpm with help of three-point hitch of the tractor.…”
Section: Sources Of the Required Data For Modeling The Modified Horiz...mentioning
confidence: 99%